(untitled) (Fiep Bulletin - online, 2020)
Acquired Immunodeficiency Syndrome (AIDS) demands a growing concern with quality of life due to the increased life span provided by the use of antiretroviral therapy and the search for health systems, as well as prevention and control methods. strategies to facilitate adjustment and increase the well-being of people with HIV / AIDS. This study aimed to characterize and compile the scientific production about the quality of life in individuals with HIV / AIDS, in online journals, from 2014 to 2018. This is an integrative literature review, performed on the Virtual Library website. in Health, in the Latin American and Caribbean Health Information Literature and International Health Science Literature databases. The descriptor used was “Quality of Life and HIV”, with a sample composed of twenty-two publications, selected according to given criteria. Two thematic categories were identified - “HIV / AIDS-related quality of life assessment”; and “Strategies used to improve quality of life in individuals with HIV / AIDS”. It was observed that the development of studies in the area of ??quality of life for this population can support humanized care practices, based on a broad perspective of the health-disease process.